La responsabilidad extracontractual del estado y las penas que se imponen en el marco de la justicia indígena - Argüello Carrasquel, Beatriz Lourdes (2021)
In order to determine whether there is a State responsibility within the framework of justice, it is pertinent to remember to what extent the State is allowed to intervene or not in indigenous peoples, communes and communities. It is impossible to reach an exact determination of this responsibility since Ecuador through the Constitution recognizes freedom of application of justice, but imposes certain limitations and it is precisely within the framework of recognized human rights. The current regulations and the permissibility in the framework of application of indigenous justice in constitutionally recognized communities, limits their actions and obliges the aforementioned indigenous communities to respect the human rights that they have won internationally through multiple struggles and that have been ratified in the internal legal system of each country.........